Baitussalam Ketintang Surabaya Junior High School Remains on Line Learning Services in Plague of Virus Corona / Covid 19 - Herlis Silviana (LPPM of NAROTAMA UNIVERSITY, 2020)
Facing the pandemic period of the Covid-19 outbreak, SMP Baitussalam Ketintang Surabaya is required to continue to carry out educational and administrative services for students. Various strategic steps are required. Hopefully, these strategic steps can overcome the situation in the even semester 2020, completion of student final assignments, and other administrative processes. The learning process during the Covid-19 pandemic will continue to be carried out through an online process until the second week of May 2020. The learning process has so far used online applications such as Zoom, Whatsapp, Webwx Cisco, and others. The assessment process and student attendance are still monitored by the subject teaching teacher during this period. If for some reason, the WHO has to do tasks at school, WHO protocols must be observed, namely wearing a mask and a distance of more than 1 meter. Registration for new students of SMP Baiutussalam Ketintang Surabaya is still ongoing until a selection test will be held, waiting for safe conditions. Currently according to the request for registration to be carried out online. SMP Baiutussalam Ketintang Surabaya has tried its best in serving the education and administration process. Strategic steps have been made to guide the outline of education services during the Covid-19 pandemic. With the steps mentioned above, it is hoped that the learning process at students' homes and other administrative processes can be completed as well as possible.